Taming the Antiferromagnetic Beast: Computational Design of Ultrashort Mn−Mn Bonds Stabilized by N‐Heterocyclic Carbenes. Issue 47 (13th July 2021) - Francisco, Marcos A. S.; Fantuzzi, Felipe; Cardozo, Thiago M.; Esteves, Pierre M.; Engels, Bernd; Oliveira, Ricardo R.
Abstract: The development of complexes featuring low‐valent, multiply bonded metal centers is an exciting field with several potential applications. In this work, we describe the design principles and extensive computational investigation of new organometallic platforms featuring the elusive manganese‐manganese bond stabilized by experimentally realized N‐heterocyclic carbenes (NHCs). By using DFT computations benchmarked against multireference calculations, as well as MO‐ and VB‐based bonding analyses, we could disentangle the various electronic and structural effects contributing to the thermodynamic and kinetic stability, as well as the experimental feasibility, of the systems. In particular, we explored the nature of the metal‐carbene interaction and the role of the ancillary η 6 coordination to the generation of Mn2 systems featuring ultrashort metal‐metal bonds, closed‐shell singlet multiplicities, and positive adiabatic singlet‐triplet gaps. Our analysis identifies two distinct classes of viable synthetic targets, whose electrostructural properties are thoroughly investigated. Abstract : The Mn2 survival guide . DFT calculations were used to design synthetically achievable compounds featuring ultrashort Mn−Mn bonds stabilized by N‐heterocyclic carbenes (NHCs). We investigated the nature of the metal–carbene interaction and the role of the ancillary η 6 coordination in the generation of ultrashort Mn2 bonds in organometallic platforms featuring closed‐shell singlet multiplicities and positive adiabatic singlet–triplet gaps. Our analysis identified two classes of potential synthetic targets, whose electrostructural properties were thoroughly examined.